THE INFLUENCE OF INTERNAL CONTROL SYSTEM, COMPETENCE AND TRANSPARENCY ON VILLAGE FUND MANAGEMENT ACCOUNTABILITY IN RUNGKUT DISTRICT, SURABAYA CITY - DEVI PERTIWI ANANDA PUTRI; TITUK DIAH WIDAJANTIE (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Sub-districts require aspects of good governance by applying the principle of accountability in financial management as accountability for policies and programs that have been implemented. The purpose of this research was to examine and analyze the influence of the internal control system, competence and transparency on the accountability of urban village fund management in the Rungkut sub-district, Surabaya city. The research sample consisted of 30 village officials from the Rungkut sub-district, who came from 5 employees from 6 villages. Data analysis technique using PLS. The results of the study show that the internal control system and competence have no effect on the accountability of village fund management, while transparency affects the accountability of village fund management in Rungkut sub-district, Surabaya city